2020
DOI: 10.3389/fendo.2020.588443
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Maternal Weight and Diabetes Are Risk Factors for Macrosomia: A Cross-Sectional Study of 42,663 Pregnancies in Uruguay

Abstract: Objective: To evaluate the risk of macrosomia in newborns from women with gestational diabetes, pregestational diabetes, overweight, and obesity in Uruguay in 2012, as well as its association with prolonged pregnancy, maternal age, multiparity, and excessive gestational weight gain (EGWG). Methods: We performed a cross-sectional study of 42,663 pregnant women. The risk of macrosomia was studied using logistic regression. Results: Mean maternal age was 26.7 ± 6.8 years. Pregestational overweight and obesity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 70 publications
1
16
0
3
Order By: Relevance
“…Thus, the combinative effect of extra glucose and insulin leads to the increased accumulation of adipose tissue and protein in the fetuses, resulting in fetal accelerated growth and macrosomia (33,34). Pereda et al (29) conducted a cross-sectional study involving 42,663 pregnant women and reported that male fetuses were associated with increased risk of macrosomia (aOR = 1.89, 95% CI: 1.72-2.08), and such association was also found in our study (OR = 1.69, 95% CI: 1.60-1.78) (Table S2). We found that for pregnant women without GDM/GDM history, the protective effect of maternal first-trimester low BMI against macrosomia was the strongest in female infants born in summer and in male infants born in spring and autumn.…”
Section: Comparison With Previous Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the combinative effect of extra glucose and insulin leads to the increased accumulation of adipose tissue and protein in the fetuses, resulting in fetal accelerated growth and macrosomia (33,34). Pereda et al (29) conducted a cross-sectional study involving 42,663 pregnant women and reported that male fetuses were associated with increased risk of macrosomia (aOR = 1.89, 95% CI: 1.72-2.08), and such association was also found in our study (OR = 1.69, 95% CI: 1.60-1.78) (Table S2). We found that for pregnant women without GDM/GDM history, the protective effect of maternal first-trimester low BMI against macrosomia was the strongest in female infants born in summer and in male infants born in spring and autumn.…”
Section: Comparison With Previous Studiessupporting
confidence: 86%
“…One possible explanation is that fetuses of nullipara were more likely to be exposed to a different maternal immune environment which might restrict the fetal growth in the uterine (28). Another possible explanation is that higher parity has been reported to be strictly related to GDM, which played an important role in the development of macrosomia (29). Schwartz et al (13) found that multipara had a higher risk of GDM compared with nullipara (73% versus 40%, P < 0.001) based on a meta-analysis of 19,053 singleton participants.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…At present, a large number of studies have found that maternal weight was a high-risk factor of macrosomia ( 21 – 24 ). Additionally, a study found that insulin resistance was a link between maternal overweight and fetal macrosomia in nondiabetic pregnancies ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“… 11–13 It is also responsible for prolonging labor, increasing the risk of obstructed labor and cesarean delivery, 14 and has notable effects on the fetus. 12 , 15 , 16 Recent animal experiments have shown that lean and obese animals are typically less fertile, but not necessarily in humans. 17 Few high-quality studies have explored the nonlinear relationship between body mass index and infertility.…”
Section: Introductionmentioning
confidence: 99%